92.3k views
5 votes
Solve: 4x - 2x + 6 = x + 12 A) x = 6 B) x = 2 C) no solution D) x = −6

User Dean Ward
by
5.7k points

2 Answers

3 votes

Answer:

A) x = 6

Explanation:

Step 1: Get all x terms to one side, and all constants to the other side

4x - 2x + 6 = x + 12

4x - 2x - x + 6 - 6 = x - x + 12 - 6 (subtract 'x' and '6' from both sides)

4x - 2x + x = 12 - 6 (simplify)

x = 6 (combine like terms, 4x - 2x + x is 'x', 12 - 6 is '6')

User Vinod Sharma
by
6.2k points
3 votes

Answer:

A) x = 6

Explanation:

4x - 2x + 6 = x + 12

Combine like terms

2x +6 = x+12

Subtract 6 from each side

2x+6-6 = x+12-6

2x = x+6

subtract x

2x-x = x+6-x

x = 6

User Dhaval Parmar
by
5.2k points